The angiogenic genes predict prognosis and immune characteristics in esophageal squamous cell carcinoma: Evidence from multi-omics and experimental verification - Wang, Shuaiyuan; Liang, Yinghao; Zhang, Jiaxin; Wang, Wenjia; Hong, Yichen; Sun, Miaomiao; Shu, Jiao; Chen, Kuisheng (Frontiers in Oncology, 2022)
Esophageal squamous cell carcinomas (ESCC) is an aggressive disease with five-year overall survival (OS) <15%. The main cause is metastasis rather than local tumor, and angiogenesis plays an important role. Angiogenesis has a significant impact on tumor metastasis, treatment and prognosis. However, the expression pattern of angiogenesis genes , its effect on treatment and its relationship with prognosis in ESCC have not been systematically reported. We performed the first and most comprehensive multi-omics analysis of angiogenic genes in patients with ESCC and identified four angiogenic phenotypes that vary in outcome, tumor characteristics, and immune landscape. These subtypes provide not only patient outcomes but also key information that will help to identify immune blocking therapies. In addition, angiogenesis index (AI) was proposed to quantify tumor angiogenesis ability, and its accuracy as a predictor of prognosis and immunotherapy was verified by external cohort and corresponding cell lines. Our study provides clinicians with guidance for individualized immune checkpoint blocking therapy and anti-angiogenesis therapy for ESCC.